Pengaruh Komposisi Mineral Tanah Terhadap Konduktivitas Listrik Dan Ketersediaan Nutrisi - Zebua, Riki Arman; Zega, Ayu Nofita Sari (CV. SINAR HOWUHOWU, 2024)
This research aims to analyze the effect of soil mineral composition on electrical conductivity and nutrient availability. Soil samples of various types (sandy, clay and clay) were analyzed to determine the mineral composition using the X-ray diffraction (XRD) method, as well as measurements of electrical conductivity and the availability of key nutrients such as potassium, calcium and magnesium. The research results show that soil with high clay mineral content, such as montmorillonite and kaolinite, has higher electrical conductivity and nutrient availability values ​​compared to sandy soil. Statistical analysis shows a positive relationship between clay mineral composition and electrical conductivity and nutrient availability. This discovery has practical implications in agricultural soil management, where electrical conductivity can be used as an indicator to predict nutrient availability quickly and efficiently.